PENGEMBANGAN MODEL PENINGKATAN MUTU PENDIDIK DAN TENAGA KEPENDIDIKAN BERBASIS ANALISIS KEBUTUHAN PADA PROGRAM STUDI PENDIDIKAN SEJARAH - Johan Pattiasina; Tanwey Gerson Ratumanan; Poltjes Pattipeilohy (Universitas Nusa Cendana, 2025)
The quality of educators and education personnel is a key factor in improving the quality of study programs in higher education, especially in education study programs. This research aims to analyze the quality needs of educators and education personnel and develop a model to improve the quality of educators and education personnel in the History Education Study Program. The research uses a qualitative approach with research and development design which refers to the Borg and Gall Development Model. The research stages include needs analysis, planning, initial model development, and validation and test of model practicality. Data was collected through in-depth interviews, document analysis, and limited observation involving lecturers, education staff, and study program leaders. Data analysis was carried out using thematic analysis. The results of the study show that there is a gap between quality standards and actual conditions, especially related to career development and lecturer performance, workload imbalances, limited education personnel, and insystematic development of academic competencies and services. Based on these findings, a conceptual model for improving the quality of educators and education personnel was developed based on an input–process–output–impact approach that is systematic, contextual, and sustainable.